Pharmacological inhibition of carbonic anhydrases with a positively charged pyridinium sulfonamide phenocopies the neuroprotective effects of Car9 genetic ablation in a murine setting of oxygen/glucose deprivation followed by re-oxygenation and is associated with improved neuronal function in ischemic rats - Sara Amiranda; Mariangela Succoio; Serenella Anzilotti; Ornella Cuomo; Tiziana Petrozziello; Valentina Tedeschi; Arianna Finizio; Giorgia Mele; Seppo Parkkila; Lucio Annunziato; Giuseppina De Simone; Giuseppe Pignataro; et al. (Heliyon)
Carbonic anhydrases constitute a family of metalloenzymes vital for maintaining acid-base balance and regulating pH in physio-pathological processes. These findings suggest carbonic anhydrases as potential therapeutic targets for treating pH-associated disorders, including cerebral ischemia, to mitigate hypoxia- and reoxygenation-induced neuronal damage. A focus on carbonic anhydrase IX showed that ischemic stress altered subcellular distributions of this enzyme in rodent neuronal populations. Given the enzyme's canonical membrane localization, we implemented pharmacological inhibition using a membrane-impermeant sulfonamide inhibitor in neuronal models of brain ischemia. The treatments exerted neuroprotective effects on neurons from Car9 knockout mice. Moreover, administration of the sulfonamide inhibitor to rats subjected to transient middle cerebral artery occlusion decreased infarct volumes and improved neurological deficits. Our results support the involvement of carbonic anhydrase IX in postischemic damage and pave the way for possible pharmacological interventions with selective inhibitors in the management of brain ischemia.